Classification of rice cultivars by using chemical, physicochemical, thermal, hydration properties, and cooking quality - Jiamyangyuen, Sudarat; Wichaphon, Jetsada; Boonmeejoy, Jitnapa (Food and Applied Bioscience Journal, 2019)
Eight rice cultivars were tested to identify changes in chemical properties (amylose, protein and lipid content), physicochemical properties (grain hardness, peak viscosity, final viscosity, and setback and breakdown values), thermal (gelatinization temperature), and hydration (water absorbance) properties, during a 6 month storage period. The affect over time on cooking quality was also analyzed. The eight cultivars included four cultivars classified as high amylose content (HM 105, RD15 and PTT1), one medium amylose content (KTH17) and four low amylose content (PL2, RD31, SP1 and CN1). The results showed that during storage, the amylose, grain hardness, peak viscosity and final viscosity increased, while break down values decreased. Protein and lipid content and setback properties were unchanged. The gelatinization temperature positively correlated with amylose content. The highest onset, peak and conclusion temperature showed in RD31 (72.67 ºC, 77.08 ºC and 84.03 ºC, respectively). For hydration properties, the high amylose content rice showed the highest capacity to absorb water. The optimum cooking time positively correlated with amylose content. Classification of the rice cultivars using PCA resulted in two distinct groups, with the high amylose cultivars being well separated from the low and medium amylose cultivars. Applying our results to rice flour, incorporation of chemical and physicochemical properties in the analysis of rice flour allows better discrimination of the rice differently from using amylose content solely. Keywords: rice classification, rice flour, amylose, pasting property, principal component analysis